ASPECTS OF CRIMINAL LAW WITHIN MEDICAL PRACTICES - Eriawan Agung Nugroho; Anggraeni Endah Kusumaningrum (Jurnal Ilmiah Galuh Justisi, 2021)
Aspects concerning legal protection for doctors in the case of their day to day practice as medical professionals is still considered lacking. This article aims to dissect provisions stated within Article 50 under Law No. 29 of The Year 2004 concerning medical practice, which discusses legal protection for practicing doctors, more specifically about reconstructing legal events concerning disputes between doctors and their patients, or criminal charges put forth by patients against doctors and how these disputes can be resolved based on the values of justice. It can be inferred that the contents of Article 50 under Law No. 29 of The Year 2014 concerning Medical Practice is that legal protection for practicing doctors is still very limited, this rings true by the method in which police would use to investigate cases of malpractice still borrows from conventional means regulated by The Indonesian Legal Code for Criminal Procedure. Pertaining to the problem stated above, it is the hope of the publisher that the government as a whole (Judiciary, Executive, and Legislative branches) can perfect the above mentioned legislations so that better protection can be afforded to doctors and other medical professionals alike.Key Words : Legal Protection, Malpractice, Medical Dispute